2012
DOI: 10.1186/1746-1596-7-114
|View full text |Cite
|
Sign up to set email alerts
|

NK/T-cell lymphoma of bilateral adrenal glands in a patient with pyothorax

Abstract: Primary lymphoma of adrenal glands is rare, and non-B-cell lymphoma associated with pyothorax is also very rare. Here we report the first autopsy case of non-B-cell lymphoma in bilateral adrenal glands of a 79-year-old woman with pyothorax who had an aggressive clinical course. Immunohistochemically, tumor cells showed CD3+, CD45RO+, CD5-, CD7-, CD4-, CD8-, CD10-, CD20-, CD30-, CD79a-, CD138-, CD56-, granzyme B-, TIA-1+ and ALK-. In addition, tumor cells were strongly EBER1-positive by in situ hybridization. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
(10 reference statements)
1
12
0
Order By: Relevance
“…NK/T-cell lymphomas that express CD30, with or without CD56 expression, have been reported in previous studies in the nasal cavity, spleen, prostate and adrenal glands ( 7 10 , 18 20 ). However, to the best of our knowledge, no studies have reported this NK/T-cell lymphoma phenotype occurring in the stomach.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…NK/T-cell lymphomas that express CD30, with or without CD56 expression, have been reported in previous studies in the nasal cavity, spleen, prostate and adrenal glands ( 7 10 , 18 20 ). However, to the best of our knowledge, no studies have reported this NK/T-cell lymphoma phenotype occurring in the stomach.…”
Section: Discussionsupporting
confidence: 54%
“…In the present study, the tumor cells possessed irregular kidney-shaped nuclei, which expressed CD3ε and diffusely expressed CD30, but did not express CD56, therefore leading to an initial diagnosis of ALCL. However, there have been studies reporting NK/T-cell lymphoma in the nasal cavity, prostate, spleen and adrenal glands, where the tumor expresses CD30, with or without CD56 expression ( 7 10 ). To the best of our knowledge, no studies have reported this type of lymphoma in the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Extranodal NK/T-cell lymphomas characteristically involve the upper aerodigestive tract, with the nasal cavity being the prototypic site [3]. Rarely, the tumour occurs in prostate, adrenal glands and lung [4][5][6]. According the WHO criterion, the neoplastic lymphoid cells usually co-express NK cell markers such as CD56 and T cellassociated antigens like CD3, CD2 with expression of cytotoxic markers such as TIA-1, Perforin and Granzyme-B [6].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, morphologically, middle to large-sized neoplastic cells with atypia and mitosis can be detected in T cell lymphoma and ANKL. However, as previously mentioned, the characteristic T-cell makers, rearranged TCR gene, and have no relation to EBV infection are distinguishing features [14,15]. …”
Section: Discussionmentioning
confidence: 99%